Pengaruh Dukungan Sosial dan Selfefficacy Terhadap Orientasi Masa Depan Pada Remaja - Muhammad Dwirifqi Kharisma Putra; Nia Tresniasari (‎‎‎TAZKIYA Journal of Psychology, 2015)
Teenage years determines success in the future. Good teenagers are who are responsible to their own success in the future, known as future orientation. Given how important future orientation is, researchers examined variables which affect future orientation, thus future orientation can be optimalized. Dimensions of social support and self-efficacy chosen as independent variables. Respondents of this study were 326 students of one of high school in Jakarta. Future orientation, measured using Orientation Test–Revised developed by Scheir, Carver, and Bridges (1994). Social Support, measured using The Social Provisions Scale developed by Cutrona and Russel (1987). Self-efficacy, measured using General Self-efficacy Scale developed by Bosscher and Smit (1998). Instruments' validity were tested using Confirmatory Factor Analysis and data was analysed using Multiple Regression Analysis. α=0.05, result of this study shows future orientation was affected by dimensions of social support, self-efficacy, and interaction between reassurance and self-efficacy with R-square = 30.3%.